Colonization of Metarhizium anisopliae on the surface of pine tree logs: A promising biocontrol strategy for the Japanese pine sawyer, Monochamus alternatus. Issue 2 (February 2020) - Kim, Jong Cheol; Baek, Sehyeon; Park, So Eun; Kim, Sihyeon; Lee, Mi Rong; Jo, Minsung; Im, Jae Seong; Ha, Panjung; Kim, Jae Su; Shin, Tae Young
Abstract: We investigated the colonization potential of five Metarhizium anisopliae isolates on pine tree surfaces under laboratory conditions, determined the influence of the pine bark extract on fungal growth and evaluated the insecticidal activity following colonization on the Japanese pine sawyer. Finally, the effect of colonization on adults pine sawyer was evaluated using the top three performing isolates (JEF-197, JEF-271 and JEF-279) under laboratory and field conditions. As a result, isolate JEF-197 showed the highest conidial production on the pine surfaces, and five isolates, including JEF-197, showed higher hyphal growth on autoclaved pine bark extract agar, compared to a water agar. Pine bark treated with the isolates showed 40–70 % mortality of adults pine sawyer. Under mimicked overwintering conditions, in the JEF-197 treatment group, 40 % of the inserted larvae became adults and all were dead after 59 d. In a field test, colonized isolate JEF-197 also showed 37 % insecticidal activity against emerged adults from the pine logs as overwintering sites. This work suggests that M. anisopliae isolate JEF-197 possibly colonized the pine surface and application of a conidial suspension on the pine logs as overwintering sites could be an effective strategy to control the pine sawyer. Graphical abstract: Image 1 Highlights: Metarhizium anisopliae isolates could colonize pine bark surface. Pine bark extract promoted the growth and colonization of M. anisopliae. Colonized JEF-197 induced 37 % mortality of emerged adults in pine logs. The isolates can be applied on pine logs to control the pine sawyer.